Burden of Herpes Zoster Among Patients with Psoriasis in the United States - David Singer; Philippe Thompson-Leduc; Siyu Ma; Deepshekhar Gupta; Wendy Y. Cheng; Selvam R. Sendhil; Manasvi Sundar; Ella Hagopian; Nikita Stempniewicz; Mei Sheng Duh; Sara Poston (Adis, Springer Healthcare, 2023)
Abstract Introduction Patients with psoriasis (PsO) are at increased risk of herpes zoster (HZ), but recent data on the incidence of HZ among patients with PsO and the impact of HZ on healthcare resource use (HRU) and costs for patients with PsO have not been described. Methods This retrospective, longitudinal, cohort study estimated HZ incidence in cohorts of adults with vs without PsO (PsO + vs PsO-) and HRU and costs among those with PsO, with vs without HZ (PsO + /HZ + vs PsO + /HZ-) using Optum's de-identified Clinformatics Data Mart Database during 2015-2020. Patients with psoriatic arthritis were excluded from all four cohorts. Comparisons between cohorts used generalized linear models to adjust outcomes based on various baseline characteristics. Results The incidence rate of HZ was significantly higher in the PsO + (n = 144,115) vs PsO- (n = 23,837,237) cohorts at 11.35 vs 7.67 per 1000 patient-years; adjusted incidence rate ratio (aIRR): 1.21, 95% confidence interval (CI): 1.16-1.25. HRU (outpatient, emergency department, and inpatient) was significantly higher in the PsO + /HZ + (n = 1859) vs PsO + /HZ- (n = 78,664) cohorts during 1 month and 3 months after HZ diagnosis (e.g., outpatient visits during month: 2.83 vs 1.30 per patient; aIRR: 1.96; 95% CI 1.86-2.06). Mean all-cause costs were also significantly higher in the PsO + /HZ + vs PsO + /HZ- cohort during both month ($5020 vs $2715 per patient; adjusted cost difference: $1390; 95% CI $842-$1964) and 3 months ($12,305 vs $8256; adjusted cost difference: $1422; 95% CI $280-$2889) after HZ diagnosis. Conclusion These findings show the increased incidence of HZ among patients with PsO and the clinical and economic burdens of HZ in this population. Considering the high prevalence of PsO, insights into the impact of HZ in these patients provide valuable evidence to inform clinical decision-making. Graphical abstract